Efektifitas Penatalaksanaan Proses Asuhan Gizi Terstandar terhadap Perbaikan Asupan Pasien Sindrom Metabolik di RSUD Sidoarjo - Dian Handayani; Pudji Astutik; Yuni Nurwati; Marselina Azalia Mahar (Universitas Muhammadiyah Semarang, 2018)
Nutrition service in hospital is a service provided in accordance with the patients’ condition based on clinical conditions, nutritional status and metabolic status of the body. These services can be achieved by providing nutritional care using the Nutrition Care Process (NCP) method.Nutrition interventions are important to help healing process, maintaining and improving health status of the patients. This study aims to determine the difference intake of the patients in the Lotus Terpene Room II and Tulip I RSUD Sidoarjo before and after nutrition interventions. The design of this study using descriptive observational study with 31 respondents taken by Purposive Sampling. Data collection was done by anthropometry measurement, data from medical record and recall 3x 24 hours. The results showed that 48% of respondents with metabolic syndrome aged 50 – 59 years and mostly with diabetes mellitus (61%), 45% of them had a good initial intake and increased after nutrition intervention. The most common nutritional diagnosis is abnormallaboratory values in blood sugar and blood fat profiles. The result of paired difference test showed significant difference of p value 0,000 (p <0,05). Conclusion : 55% respondents increased their intake in the end of observation. Nutrition intervention can improve the patients’ intake.Keywords : initial intake, final intake, standardized nutrition care, metabolic syndrome